Quality and extent of implementation of a nurse-led care management intervention: care coordination for health promotion and activities in Parkinson's disease (CHAPS) - Karen I. Connor; Hilary C. Siebens; Brian S. Mittman; David A. Ganz; Frances Barry; E. J. Ernst; Lisa K. Edwards; Michael G. McGowan; Donna K. McNeese-Smith; Eric M. Cheng; Barbara G. Vickrey (BMC, 2020)
Abstract Background A recent nurse-led, telephone-administered 18-month intervention, Care Coordination for Health Promotion and Activities in Parkinson's Disease (CHAPS), was tested in a randomized controlled trial and improved care quality. Therefore, intervention details on nurse care manager activity (types and frequencies) and participant actions are needed to support potential dissemination. Activities include nurse care manager use of a holistic organizing framework, identification of Parkinson's disease (PD)-related problems/topics, communication with PD specialists and care coordination, participant coaching, and participant self-care actions including use of a notebook self-care tool. Methods This article reports descriptive data on the CHAPS intervention. The study setting was five sites in the Veterans Affairs Healthcare System. Sociodemographic data were gathered from surveys of study participants (community-dwelling veterans with PD). Nurse care manager intervention activities were abstracted from electronic medical records and logbooks. Statistical analysis software was used to provide summary statistics; closed card sorting was used to group some data. Results Intervention participants (n = 140) were primarily men, mean age 69.4 years (standard deviation 10.3) and community-dwelling. All received the CHAPS Initial Assessment, which had algorithms designed to identify 31 unique CHAPS standard problems/topics. These were frequently documented (n = 4938), and 98.6% were grouped by assigned domain from the Organizing Framework (Siebens Domain Management Model™). Nurse care managers performed 27 unique activity types to address identified problems, collaborating with participants and PD specialists. The two most frequent unique activities were counseling/emotional support (n = 387) and medication management (n = 349). Both were among 2749 total performed activities in the category Implementing Interventions (coaching). Participants reported unique self-care action types (n = 23) including use of a new notebook self-care tool. Conclusions CHAPS nurse care managers implemented multiple activities including participant coaching and care coordination per the CHAPS protocol. Participants reported various self-care actions including use of a personalized notebook. These findings indicate good quality and extent of implementation, contribute to ensuring reproducibility, and support CHAPS dissemination as a real-world approach to improve care quality. Trial registration ClinicalTrials.gov as NCT01532986 , registered on January 13, 2012.